Making it sound: the performative qatal and its explanation - Andrason, Alexander W. (The journal of Hebrew scriptures, 2012)
The performative sense of the qatal is compatible with the remaining components of the semantic load offered by the gram. Employing a chaining procedure built on the framework of universal paths and adopting a cognitive perspective whereby the verbal meaning is a network of conceptually and diachronically related senses, the author demonstrates that since the qatal is defined as a manifestation of an anterior cline and since it is possible to posit a performative stage on this trajectory, the anterior cline may also accommodate the performative sense.